Ebola and Marburg virus antibody prevalence in selected populations of the Central African Republic - Jean Paul Gonzalez (2018)
With the natural history of the filovirus family seemingly unknown, filovirus ecology in its natural environment remains a rudimentary field of research. In order to investigate the maintenance cycle of filovirus in Central Africa, a study was conducted within the rain forest of the Central African Republic. The epidemiological study determines the frequency and distribution of filovirus seroprevalence in a selected human population. Using an ELISA, serum samples from Pygmy and non-Pygmy populations were tested for Ebola-Zaire virus and Marburg (MBG) virus antibody. Filovirus antibody reacting sera were found in all zones investigated, and in all populations studied (Ebola virus IgG 5.3%; Marburg virus IgG 2.4%). Pygmies appeared to have a significantly higher seroprevalence (P < 0.03) against Ebola-Zaire virus (7.02%) than non-Pygmies (4.2%). MBG virus or related unknown filovirus strains also seem to be present in the western part of Central Africa. MBG virus antibodies were present in different Pygmy groups (ranging from 0.7 to 5.6%, mean 2.05%) and in several non-Pygmy populations (ranging from 0.0 to 3.9%, mean 3.4%) without an overall significant difference between the two groups (P = 0.14). The potentialities of nonpathogenic filovirus strains circulating in the Central African Republic are discussed. (C) 2000 Editions scientifiques et medicales Elsevier SAS.